IMPLEMENTASI PERATURAN MENTERI SOSIAL RI NO. 12 TAHUN 2019 TENTANG IZIN UNDIAN GRATIS BERHADIAH DALAM MENINGKATKAN KUALITAS PELAYANAN PADA DINAS SOSIAL PROVINSI LAMPUNG - Malik Malik; Rina Karya Wardani (e-JKPP, 2022)
The purpose of this research is to find out and analyze, (1) Implementation of the Regulation of the Minister of Social Affairs RI No. 12 of 2019 concerning Permits for Free Lottery with Prizes in Improving the Quality of Community Services at the Lampung Province Social Service. (2) What aspects hinder the implementation of the Regulation of the Minister of Social Affairs RI No. 12 of 2019 concerning Permits for Free Lottery with Prizes in Improving the Quality of Community Services at the Lampung Province Social Service.The approach used in this research is a qualitative method with descriptive analysis method. The research subjects were (1) the Head of the Lampung Province Social Service, (2) the Head of the Free Lottery Division with prizes from the Ministry of Social Affairs (3) the Head of the Eka Bank Services Division, (representation of the Bank in Lampung), (4) Chandra Service Manager, (5) two Prov. Ministry of Social Affairs staff. Lampung.. Data analysis was carried out with data reduction activities, data presentation, and drawing conclusions/verification.The results of the study concluded that the implementation of the Regulation of the Minister of Social Affairs RI No. 12 of 2019 concerning Permits for Free Sweepstakes with Prizes in Improving the Quality of Community Services at the Lampung Provincial Social Service, through the Communication dimension, it has been carried out through directing service staff and making jargon pasted on the wall. Disposition, namely the staff has implemented and supported the policy well, because it is a top down program. Quality of resources, namely the leadership has placed employees according to their abilities and expertise. There is still a bureaucratic structure that often overlaps levers and authority at certain times, so that the implementation of tasks is not optimal. The inhibiting aspects are (1) The company/Agency still lacks understanding of the process of implementing the free lottery, (2) Not yet optimal cooperation in programs and activities between governments, non-governmental organizations, (3) The relatively low quality of human resources implementing free lottery permits prize.